Population structure and microscale morphological differentiation in a freshwater snail from the Chilean Altiplano - Valladares, Moises A.; Fabres, Alejandra A.; Sanchez-Rodriguez, Fernanda; Collado, Gonzalo A.; Mendez, Marco A. (My University, 2024)
BackgroundThe diversity and population genetic structure of many species have been shaped by historical and contemporary climatic changes. For the species of the South American Altiplano, the historical climatic changes are mainly related to the wet events of great magnitude and regional influence that occurred during the Pleistocene climatic oscillations (PCOs). In contrast, contemporary climate changes are associated with events of lesser magnitude and local influence related to intensifications of the South American Summer Monsoon (SASM). Although multiple studies have analyzed the effect of PCOs on the genetic patterns of highland aquatic species, little is known about the impact of contemporary climate changes in recent evolutionary history. Therefore, in this study, we investigated the change in population structure and connectivity using nuclear and mitochondrial markers throughout the distribution range of Heleobia ascotanensis, a freshwater Cochliopidae endemic to the Ascotan Saltpan. In addition, using geometric morphometric analyses, we evaluated the concomitance of genetic divergence and morphological differentiation.ResultsThe mitochondrial sequence analysis results revealed the presence of highly divergent co-distributed and geographically nested haplotypes. This pattern reflects an extension in the distribution of groups that previously would have differentiated allopatrically. These changes in distribution would have covered the entire saltpan and would be associated with the large-scale wet events of the PCOs. On the other hand, the microsatellite results defined five spatially isolated populations, separated primarily by geographic barriers. Contemporary gene flow analyses suggest that post-PCO, climatic events that would have connected all populations did not occur. The morphometric analyses results indicate that there is significant morphological differentiation in the populations that are more isolated and that present the greatest genetic divergence.ConclusionsThe contemporary population structure and morphological variation of H. ascotanensis mainly reflect the post-PCO climatic influence. Although both markers exhibit high genetic structuring, the microsatellite and morphology results show the preponderant influence of fragmentation in recent evolutionary history. The contemporary genetic pattern shows that in species that have limited dispersal capabilities, genetic discontinuities can appear rapidly, erasing signs of historical connectivity.
Keywords: fragmentation; aquatic invertebrate; south american summer monsoon; geometric morphometrics; pleistocene climatic oscillations